LibreDTE: Software Tools and Support for Electronic Invoicing in Chile - De la Fuente, Esteban (2022)
This work introduces LibreDTE, an initiative providing software tools and support for electronic invoicing in Chile. LibreDTE is mainly built upon libredte-lib, a free software library that directly connects with the Chilean Internal Revenue Service, thus enabling automatic emissions of official e-invoices and other electronic tax documents. LibreDTE is either: (1) the first (and so far, the only one) Chilean framework for free-software-driven e-invoicing, and (2) an official software solution with featured e-business capabilities. In this paper, we describe both, the community (or free software) version, and the official (or commercial) version of LibreDTE. We focus on their primary building blocks and major technical differences, and we show, in a tutorial way, some of the key design considerations behind their common e-invoice generation. We also discuss some lessonslearned from earlier implementations, as well as the latest (and promising) features incorporated within the official version.